IS THE REPEAT A YEAR PRACTICE EFFECTIVE IN LATVIAN BASIC EDUCATION? - Mihailovs, Ivans Jānis; Krūmina, Aira Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Each country has pupils, who are not able to meet certain educational requirements (according, their health, behavior, social or other problems). One of the solutions of these problems is the repeat a year. The number of pupils remaining for the second year at the same grade in Latvia is 1% of total number of pupils. However, in Latvia have not been taken researches of the repeat a year on basic education, its causes and the activities of educational institutions. Therefore, it is not clear whether the repeat a year is effective in Latvia?The article presents the results of a comprehensive repeat a year survey, conducted in 2016, covering 70 Latvian educational institutions that implement basic education programs. The purpose of the research is to determine the causes of repeat a year phenomenon and the activities of educational institutions to prevent it in basic education in Latvia, ascertaining whether the repeat a year is effective in solving learning and behavioral problems of pupils.Methods of research – questionnaires and interviews with directors of educational institutions and other responsible persons (vice-directors of educational institutions, support staff – social pedagogues, speech therapists, etc.), who daily work with pupils remaining for the second year at the same grade.The survey has made it clear that the repeat a year is effective if the educational institution identifies its possible causes as quickly as possible and implements targeted and planned activities to prevent and implement it (including involving municipality and other specialists), as well as the interest of the pupil and their parents is cooperation in solving problems.